CONSUMER PREFERENCE ANALYSIS ON SHOPPING INTEREST IN TRADITIONAL AND MODERN MARKETS IN BADUNG REGENCY - Dewa Gede Agung Ari Guna Artha; Made Dwi Setyadhi Mustika (Adisam Publisher, 2025)
The rapid growth of modern markets in Badung Regency has led to a shift in consumer preferences from traditional markets to modern ones. This change is influenced by various factors related to social, economic, and lifestyle conditions. This study aims to examine the effect of price, income, service quality, promotion, and location on consumer shopping interest in both traditional and modern markets, both simultaneously and partially. The data used in this study consists of both primary and secondary data obtained through interviews with 100 respondents selected using purposive sampling. Data collection was conducted using questionnaires, and the analytical method employed was multiple linear regression. The results of the study indicate that the variables of price, income, service quality, promotion, and location simultaneously have a significant influence on consumer shopping interest. Partially, each of the five variables also has a positive effect on consumer preference. These findings suggest that the more favorable consumers perceive price, income, service quality, promotion, and location, the greater their tendency to choose shopping venues that align with their preferences. Consumers with specific income levels and needs tend to choose shopping places they find most beneficial, whether traditional or modern markets. This study is expected to serve as a reference for developing marketing strategies and enhancing the competitiveness of traditional markets amid the growing dominance of modern markets.